Accountability, Transparency, and Public Governance in Public Sector Accounting: A Systematic Literature Review and Bibliometric Analysis - Jumardi Jumardi (Sean Institute, 2026)
Accountability, transparency, and public governance are central to the credibility and effectiveness of public financial management. Yet, research on these interrelated themes is dispersed across public accounting, governance, digitalisation, and anti-corruption studies. This study maps the intellectual structure, thematic development, and future research directions of this field. A systematic literature review guided by PRISMA 2020 was combined with bibliometric analysis using VOSviewer. Scopus records were retrieved on 3 July 2026. After duplicate removal and eligibility screening, 314 documents published between 2019 and 2026 were retained for bibliometric mapping, while 30 core studies were synthesised narratively. The results show sustained growth in publications, peaking at 71 documents in 2025. Public Money and Management and the Journal of Public Budgeting, Accounting and Financial Management were the most productive outlets. At the same time, the United Kingdom, Indonesia, and Italy were the leading contributing countries. Keyword co-occurrence analysis revealed three clusters: digital governance and public financial management; public sector accounting and accountability; and IPSAS, transparency, and anti-corruption. The narrative synthesis indicates a shift from compliance-centred accountability towards reflective and transformative governance, enabled by digital technologies, international standard harmonisation, and stronger oversight institutions. The study consolidates an evidence-based knowledge map and offers a research agenda for public sector accounting scholars and policymakers seeking to advance accountable, transparent, and sustainable public financial governance